2010
DOI: 10.1007/bf03325307
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and acceptability of common weight-loss practices

Abstract: A disconnect between research findings and public beliefs may lead to further dieting failures for consumers. Participants (N=300) were surveyed to determine their weight loss practices, opinions of weight loss methods, and rated the acceptability of popular and empirically validated weight loss programs. Dieting, the intention to diet, and the use of popular diets and diet aids were prevalent. There was a tendency for participants to view weight as more of a problem for society than themselves. The Behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Among the most popular dietary practices in the general population, weight‐loss restrictive diets seem to be also practiced by some cancer survivors . Several randomized controlled trials demonstrated the efficiency of some specific diets on weight loss or functional outcomes in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most popular dietary practices in the general population, weight‐loss restrictive diets seem to be also practiced by some cancer survivors . Several randomized controlled trials demonstrated the efficiency of some specific diets on weight loss or functional outcomes in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…But, the value and impact of adding these data to the EHR is unknown. Our research shows that patients' beliefs about their readiness for weight loss/management and their perceptions about their weight status may be important to consider when advising about weight loss attempts among obese or overweight patients in primary care settings ( Volger et al, 2012 , Greiner et al, 2008 , Ko et al, 2008 , Post et al, 2011 , Varnado-Sullivan et al, 2010 ). Data from longitudinal studies are needed to validate these findings before determining how psychological variables can be incorporated into the EHR and used to increase the quality of obesity counseling for weight loss.…”
Section: Discussionmentioning
confidence: 90%
“…However, the conviction on the efficiency of these types of solutions for weight reduction was more frequent among individuals with a normal BMI than in those with a high BMI, which might be a consequence of a prior negative experience among the latter. In fact, despite people not perceiving the consumption of over the counter pills, drinks or supplements as particularly successful or acceptable, they are more commonly used than empirically tested interventions for weight reduction [20]. The incorrect knowledge about obesity treatments contributes to reinforce the pervasiveness of negative attitudes and stigmatization toward obese individuals in Western societies, in the sense that misconceptions regarding easy solutions for losing weight reproduce the stereotype of an obese person as lazy, unsuccessful and noncompliant with treatments [44].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, obesity awareness is not necessarily translated into a healthier BMI [19]. In fact, a discrepancy exists between individuals' beliefs about effective weight loss practices and their dieting behaviors [20]. As an example, nutrition knowledge only has modest effects on food choice, suggesting that knowing what constitutes a healthy diet does not necessarily mean that people incorporate healthy habits into their daily routines [21].…”
Section: Introductionmentioning
confidence: 99%